2020
DOI: 10.1371/journal.pone.0237876
|View full text |Cite
|
Sign up to set email alerts
|

Relative susceptibility to pesticides and environmental conditions of Frankliniella intonsa and F. occidentalis (Thysanoptera: Thripidae), an underlying reason for their asymmetrical occurrence

Abstract: To explain the asymmetrical abundance of native Frankliniella intonsa (Trybom) (Thysanoptera: Thripidae) and invasive Frankliniella occidentalis (Pergande) in the fields, we examined differential susceptibility to pesticides and environmental conditions, i.e., nine combinations of temperatures and relative humidities (RHs). We found adult female F . intonsa to be more susceptible to most of the tested insecticides as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
4
5
0
Order By: Relevance
“…2(B), (D)). In agreement with previous studies reporting on other thrips species replaced by F. occidentalis, 21,34 we can conclude that insecticide-mediated interspecific competition among thrips appears to be a key mechanism of displacements. Although the two native thrips reported here suggests that not all displacements involve invasive species, caution needs to be paid to their spread to other regions given their potential as invasive pests.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…2(B), (D)). In agreement with previous studies reporting on other thrips species replaced by F. occidentalis, 21,34 we can conclude that insecticide-mediated interspecific competition among thrips appears to be a key mechanism of displacements. Although the two native thrips reported here suggests that not all displacements involve invasive species, caution needs to be paid to their spread to other regions given their potential as invasive pests.…”
Section: Discussionsupporting
confidence: 93%
“…Together, these results demonstrate that F. intonsa is more dominant in abundance over M. usitatus under insecticide‐free situations, owing to the fast population increase of F. intonsa compared to M. usitatus . This similar result was also observed in interspecific competition between F. occidentalis and T. tabaci 35 or F. intonsa 21,34 in the treatments not exposed to insecticides. In contrast to non‐exposure tests, we surprisingly found that continuous exposure to spinetoram contributed to displacement of F. intonsa by M. usitatus (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations